2017
DOI: 10.1186/s12891-017-1600-7
|View full text |Cite
|
Sign up to set email alerts
|

Early anti-inflammatory intervention ameliorates axial disease in the proteoglycan-induced spondylitis mouse model of ankylosing spondylitis

Abstract: BackgroundAnkylosing spondylitis (AS) is characterised by immune-mediated arthritis and osteoproliferation, ultimately leading to joint ankylosis. Whether inflammation is necessary for osteoproliferation is controversial, fuelled by the unclear efficacy of anti-inflammatory treatments on radiographic progression. In proteoglycan-induced spondylitis (PGISp), a mouse model of AS, inflammation is the prerequisite for osteoproliferation as osteoproliferation was only observed following inflammation-driven interver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…To date, reliable reagents specific for mouse have become available and studies suggest that serum CRP levels may be vastly underestimated 40,41 . High serum CRP levels ranging from 5 mg mL −1 to 50 mg mL −1 have been determined in different mouse models 40,4246 , which are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To date, reliable reagents specific for mouse have become available and studies suggest that serum CRP levels may be vastly underestimated 40,41 . High serum CRP levels ranging from 5 mg mL −1 to 50 mg mL −1 have been determined in different mouse models 40,4246 , which are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it could not be ignored that the coefficients of variation vary in large ranges for both of them 50 . We review other studies, which also show large variations of serum CRP 4244 . In our previous work, we also demonstrate the large variations of other proteins in signaling pathways 53 .…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have shown that some members are osteogenic. However, results have varied among studies due to differences in experimental conditions, cell types, stimulation methods and durations, and osteogenesis measurements . We screened all family members in the current culture system using different osteoprogenitor cell types to compare the osteogenic abilities of the Wnt proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Four non‐transgenic models are most frequently used to study bone and joint pathology in rheumatic diseases: spontaneous arthritis in DBA/1 mice, CIA, collagen antibody–induced arthritis, and proteoglycan‐induced arthritis/PGIS. In all of these models, bone remodeling and new bone formation were found to be closely correlated to the inflammation process (). Of these models, osteophytes in the paws of DBA/1 mice and syndesmophytes leading to vertebral bony bridging in the PGIS model are most widely considered to be pathologic changes similar to new bone formation in the axial skeleton of patients with AS.…”
Section: Discussionmentioning
confidence: 99%
“…For the PGIS model, BALB/c mice were mixed and caged in groups of 5 mice at 24 weeks of age. Cartilage PG was prepared as previous described (Mikecz et al , 1987; Tseng et al , 2016; Tseng et al , 2017). As a standard method, the first antigen injection (100 mg PG protein) was given in complete Freund’s adjuvant (Sigma, MO, USA), and the same doses of antigen were injected as second and third boosts in incomplete Freund’s adjuvant on weeks 3 and 6.…”
Section: Methodsmentioning
confidence: 99%